Mrs. Lee Hyde, Mrs. Steve Ferry, and Mrs. Earl Dailey - Unknown:::Creator::::::::::::
Photograph shows three women holding a framed certificate. The certificate is being given to the Edenettes for doubling their active membership during the 1970 membership drive. The women from left to right are: Mrs. Lee Hyde, Mrs. Steve Ferry, and Mrs. Earl Dailey.